Hormonální antikoncepce a nĕkteré biochemické ukazatele se zvlástním zretelem k bílkovinám - Fassati, P; Spízek, J; Oktábcová, M; Fassati, M (Ceskoslovenska gynekologie, 1982)
The authors investigated a wide spectrum of biochemical indicators in 3 groups of women--34 healthy women, 27 pregnant women, and 59 women who took oral contraceptives (OCs). In the present paper, the authors paid particular attention to the group of healthy women and those taking OCs. They found a significant difference in the albumin turbidity reaction, the positive character of which is mainly due to changes in the albumin structures. Attention is drawn to possible metabolic changes in album synthesis and effects on the liver when OCs are used. (author's modified)
Keywords: Contraceptives, Oral, Hormonal; dospělí; Oral Contraceptives--side effects; Contraceptives, Oral; Family Planning; těhotenství; kontraceptiva orální; Humans; Contraceptive Agents; kontraceptiva orální hormonální; sérový albumin; Lipids; Contraceptive Methods--side effects; Contraceptive Agents, Female; Hepatic Effects; lipidy; Reproductive Control Agents; Adult; Contraception; Reproduction; ženské pohlaví; Liver; krevní proteiny; lidé; Serum Albumin; Pregnancy; játra; Blood Proteins; Female